A study on the performance of government or state backed unit trusts / Nor Azlinah Rohani - Rohani, Nor Azlinah (1996)
A unit trust fund is an investment scheme which pools money from many investors who share the same financial objectives.. The purpose of this project paper is to examine the performance and ranking of 23 government or state baclted unit trust funds in Malaysia. The performance can be analysed, whether it underperformed or outperformed the market. This study was conducted over the 5-year period starting from January 1991 to December 1995, using weekly returns of each fund and KLSE Composite Index . This study also evaluates the year to year performance by making comparisons between the performance in the year before and after 1993. Besides returns, risk are also measured. Referring to risk profile, all funds have a lower risk compared to the marlcet. The funds were well diversified as measured by R-squared and it also showed a weak positive relationship with the market. The inconsistency of unit trusts performance were observed over the review period. From the performance models used, it showed that the government or state baclced unit trust funds underperformed the market except for Amanah Saham Kedah.